Physical and Chemical Quality Testing of Goat's Milk at the Teaching Farm of The Faculty of Animal Science - Muhammad Dohi; Ine Karni; Ica Ayu Wandira; I Nyoman Sadia; Tahyah Hidjaz (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aimed to evaluate the physical, microbiological, organoleptic, and chemical quality of PE Kaligesing, PE Jawarandu, and Boer goat milk produced at the Teaching Farm of the Faculty of Animal Science, University of Mataram. The parameters included viscosity, color, total dissolved solids, Total Plate Count, organoleptic properties, water content, dry matter, crude fat, crude protein, lactose, ash, and pH. PE Kaligesing milk had the highest viscosity, indicating a thicker texture. Boer milk had the highest total dissolved solids, suggesting higher dissolved components such as lactose, minerals, protein, and fat. The color characteristics of all samples remained within the normal range of fresh milk. The organoleptic results showed that all milk samples were acceptable to panellists, with PE Kaligesing milk preferred for colour, flavour, and texture, while Boer milk showed higher aroma acceptance. Chemical analysis showed that PE Kaligesing milk had the highest crude fat and crude protein contents, PE Jawarandu milk had the highest dry matter content, and Boer milk had the highest lactose, ash, and pH values. The Total Plate Count values of all samples were below the maximum limit of the Indonesian National Standard, indicating good microbiological quality and hygienic handling. Overall, the three types of goat milk showed good quality and have potential to be developed into dairy products according to their specific characteristics. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 6: Clean Water and Sanitation